Seed moisture content during chilling and heat stress effects after chilling on the germination of common alder and downy birch seeds - O'Reilly, Conor; De Atrip, Norberto (Silva Fennica, 2007)
The effects of seed moisture content (MC) and heat treatment on the germination response of common alder (Alnus glutinosa) and downy birch (Betula pubescens) seeds were examined. Seeds of each species were adjusted to MC of 7% to 50% MC, then chilled for up to 36 weeks, after which they were allowed to germinate at 15Â°C with 8 hours lighting per day or 20 (dark)/ 30Â°C (light). Seed lot effects were evident, but treatment effects were consistent in each lot and species. The response to moist chilling treatments was larger at 15Â°C than at 20/30Â°C. Chilling had no effect on germination unless seed MC was >15%, but it was low also at 20% MC. The highest germination was achieved following 24â36 weeks chilling at the optimum or target MC (TMC) levels of about 30% in alder and 35% in birch. In a separate experiment, seeds were fully imbibed (FI) (~50% MC; standard method used in operational practice) or adjusted to TMC levels, after which some seeds of each treatment group were chilled to release dormancy. Following this, the seeds were dried back to TMC levels and then subjected to 60Â°C for up to 4 hours after which they were allowed germinate under the same conditions described above. Heat treatment damaged the prechilled FI seeds, but no damage occurred to the non-chilled seeds. However, heat stress stimulated germination in the non-chilled FI seeds of both species and the TMC seeds of alder.